Gender research in Belarus: history, social context, persons - Burova, Svetlana N. (Journal of the Belarusian State University. Sociology, 2019)
In the article, from the standpoint of the gender approach, social issues are considered, which is based on the social equality of women and men and its benefits. The history and social context of gender studies in Belarus is considered; called the names of researchers and professionals who were the first to contribute to new understanding of social reality in 1990–2010, described the achievements. The trends in the gender sector, the main difficulties in conducting gender studies and their potential are indicated.